Efficiency of the method of quantitative coproovoscopic diagnostic of nematodirosis in cattle - Ponomarenko, V. (Scientific Progress & Innovations, 2024)
Cattle breeding plays a major role in increasing the production of meat and other high-quality food products. However, various parasitic diseases often hinder the increase of livestock and the increase of milk and meat productivity of animals. Strongyloidoses of the gastrointestinal tract, in particular nematodirosis, are the most common infestations among cattle. The aim of the work was to determine the effectiveness of the proposed method of quantitative coproovoscopic diagnosis of nematodirosis in cattle. The proposed useful model refers to the field of veterinary medicine, namely, veterinary parasitology, methods of coproovoscopy, in particular, quantitative methods of detecting eggs of causative agents of nematodirosis of cattle. In laboratory conditions, well-known methods of quantitative coproovoscopy were compared, namely: the method of counting helminth eggs in feces (according to Liashenko et al., 2012), the centrifuge-flotation method (according to Taylor et al., 2015), as well as the proposed method for laboratory diagnosis of nematodirosis cattle. It was determined that when using the proposed method and the centrifuge-flotation method, 100 % of positive samples were detected. At the same time, when using the method of counting helminth eggs in feces, 70 % of positive samples were detected in the diagnosis of nematodirosis in cattle. The proposed method turned out to be the most effective in terms of indicators of the intensity of nematodirous invasion, where its sensitivity was significantly higher by 1.3 times – compared to the centrifugal-flotation method according to Taylor and by 6.5 times – compared to the method of counting helminth eggs in feces according to Liashenko. In the proposed method of quantitative coproovoscopic diagnosis of nematodirosis of cattle, a combined flotation solution is used, which exhibits coagulation properties relative to undigested fodder residues, which facilitates the microscopy process. The obtained results of experimental studies allow recommending the proposed method of quantitative coproovoscopic diagnosis of cattle nematodirosis for more accurate laboratory diagnosis of this infestation